BETON GEOPOLIMER NON-PASIR UNTUK BUIS BETON - Pratikto Pratikto; Indah Puspita Sari (Politeknik Negeri Jakarta, 2015)
Abstract Geopolymer concrete is concrete with a binder solution that does not need cement, but the use of fly ash as an adhesive for the content of silica and alumina very high. Fly Ash was activated with an alkaline solution such as Sodium Hydroxide and Sodium Silicate as catalyst. This research aims to make geopolymer concrete-buis with out sand that to be used as a water catchment form. This concrete is the variation of the concentration of NaOH used in the ratio Na2SiO3 / NaOH for 2 while the ratio of activator / fly ash is 0.3 and 2% superplasticizer content. Compaction method used with stabbing for treatment at a temperature of space left without special treatment until the age of testing as the reference point. For the characteristics of geopolymer concrete is analyzed from the results of the test specimen of compressive strength, tensile strength and flexural strength. Reduced chance of rain water infiltrating into the soil and water control, to cope with flooding and drought are through infiltration wells which is one of the environmentally friendly drainage system by increasing infiltration of rainwater into the soil and reduce runoff to cause flooding. Buis concrete without cement and without sand will be a good and economical solution Keywords: Geopolymer concrete, Fly ash, superplasticizer ,water catchment Abstrak Beton geopolymer adalah beton dengan larutan bahan pengikat yang tidak menggunakan semen, tetapi menggunakan fly ash sebagai perekat karena kandungan silika dan aluminanya sangat tinggi.Fly Ash yang digunakan diaktifkan dengan larutan alkali berupa Sodium Hidroksida dan Sodium Silikat sebagai katalisatornya.Penelitian ini bertujuan untuk membuat buis beton geopolimer non pasir untuk digunakan sebagai sumur resapan air.Beton ini dengan variasi konsentrasi NaOH yang digunakan pada rasio Na2SiO3/NaOH sebesar 2 sedangkan rasio activator /fly ash adalah 0,3 dan kadar superplasticizer 2%. Metode pemadatan dengan penusukan dan untuk perawatan dibiarkan disuhu ruang tanpa perlakuan khusus sampai umur pengujian (refensi).Untuk karakteristik beton geopolimer ini dianalisa dari hasil benda uji terhadap kuat tekan, kuat tarik dan kuat lentur.Berkurangnya kesempatan air hujan berinfiltrasi ke dalam tanah dan pengendalian air, untuk mengatasi genangan dan kekeringan adalah melalui sumur resapan yang merupakan salah satu sistem drainase berwawasan lingkungan dengan memperbesar resapan air hujan ke dalam tanah dan memperkecil aliran permukaan sebagai penyebab banjir. Buis beton tanpa semen dan tanpa pasir akan merupakan solusi yang baik dan ekonomis. Kata Kunci: Beton geopolimer non pasir, Fly ash, superplasticizer , sumur resapan air